UPAYA PERANCANGAN UNDANG-UNDANG TENTANG LARANGAN MERENDAHKAN MARTABAT PENGADILAN - Asshiddiqie, Jimly (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2015)
To protect the dignity and soverignty of judiciary not only uses criminal law mechanism but also uses both civil contempt of court and ethical contempt of court integrally.Keywords : Act Proposal, Contempt of Court